A real-world analysis of FDA Adverse Event Reporting System (FAERS) events for liposomal and conventional doxorubicins - Huiling Su; Jing Jia; Yuxiang Mao; Riran Zhu; Zhengjun Li (Scientific Reports, 2024)
Abstract The clinical application of conventional doxorubicin (CDOX) was constrained by its side effects. Liposomal doxorubicin was developed to mitigate these limitations, showing improved toxicity profiles. However, the adverse events associated with liposomal doxorubicin and CDOX have not yet been comprehensively evaluated in clinical settings. The FAERS data from January 2004 to December 2022 were collected to analyze the adverse events of liposomal doxorubicin and CDOX. Disproportionate analysis and Bayesian analysis were employed to quantify this association. Our analysis incorporated 68,803 adverse event reports related to Doxil/Caelyx, Myocet and CDOX. The relative odds ratios (RORs, 95%CI) for febrile neutropenia associated with CDOX, Doxil/Caelyx, and Myocet were 42.45 (41.44; 43.48), 17.53 (16.02; 19.20), and 34.68 (26.63; 45.15) respectively. For cardiotoxicity, they were 38.87(36.41;41.49), 17.96 (14.10; 22.86), and 37.36 (19.34; 72.17). For Palmar-Plantar Erythrodysesthesia (PPE), the RORs were 6.16 (5.69; 6.68), 36.13 (32.60; 40.06), and 19.69 (11.59; 33.44). Regarding onset time, significant differences adverse events including neutropenia, PPE, pneumonia and malignant neoplasm progression. This study indicates that clinical monitoring for symptoms of cardiotoxicity of CDOX and Myocet, and PPE and interstitial lung disease of Doxil should be performed. Additionally, the onset time of febrile neutropenia, malignant neoplasm progression, and pneumonia associated with Doxil and Myocet merits particular attention. Continuous surveillance, risk evaluations, and additional comparative studies between liposomal doxorubicin and CDOX were recommended.